PENGEMBANGAN PARIWISATA BERKELANJUTAN MELALUI KETERLIBATAN WIRAUSAHA PEREMPUAN DI WISATA RELIGI SYAIKHONA KHOLIL BANGKALAN - Syarifatul Munawaroh; Triana Setiyarini; Mochammad Isa Anshori; Hilmiyah Aulia (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the perceptions of women entrepreneurs regarding sustainable tourism development and also identify sustainable tourism development through the involvement of women entrepreneurs in the Syaikhona Kholil religious tourism, Bangkalan, Madura. Tourism in Indonesia, especially the religious tourism sector, continues to develop and has great potential to support the national economy. On the other hand, women's involvement in tourism plays an important role not only in supporting the family economy but also in preserving local culture through the unique products produced. This research uses qualitative methods by collecting data through observation, interviews and documentation. The research results show that female entrepreneurs in this region have a positive perception of sustainable tourism and are committed to protecting the environment and supporting destination development